Implementación de la gestión por procesos para la toma de decisiones gerenciales en la empresa Lácteos San Isidro S.A. - Moreira Valdivieso, Héctor Adrián (2023)
The development of this research aimed at the implementation of process management in the Lácteos San Isidro S.A. company, in order to contribute to the improvement of administrative management. Methodologically, a bibliographical and field study was developed, applying analysis and synthesis as basic techniques, in the development of the three phases: the first stage, comprised the characterization of the industry and the current state of its processes, through the use of tools such as the interview and the survey, in order to carry out the corresponding diagnosis; after that, in stage two, the review of different bibliographic sources was used with the purpose of identifying several procedures, through which the model for the description of process management was structured. Finally, in phase three, its application was carried out, registering the threads that make up the organization, its survey, diagramming, and the elements that affect the model were determined, to consequently be evaluated and select improvement alternatives. From the results obtained, the absence of a process management model and monitoring and control instruments was found, which in accordance with the data obtained from the interviewee, by not having a standardized system of activities, bottlenecks are generated, delays or variation in its execution during production; based on these arguments, the study allows us to conclude that the development and implementation of procedures aligned with good manufacturing practices, operational controls of the sub-processes, and the development of BPM, POE, POES and HCCP manuals are required.